Megatrends Determining the Boundaries of Modern Organizations - Slawomir ZIOLKOWSKI (Communications of International Proceedings, 2021)
Answering the question of what a modern organization is today is much more difficult than it was even last century. What defines the limits of understanding organization? Are they artifacts, the tangible results of human labor? In the era of the post-industrial economy, such an approach is archaic. So perhaps it is a system of norms and procedures that organize and discipline the processes of organizational activity? In networks created on an ad hoc basis for the purpose of a project, it is not the method of implementation that matters, only the end result. So maybe it is a social system - people, creating a certain structure? The displacement of people by "digital workers", AI and machine learning algorithms leads us to abandon this interpretation. So maybe the initiator, the business owner determines at least the source of the organization? When the owner is a crowd with dynamic turnover, the organization becomes a cloud, dependent on the dynamics of socio-economic processes. Even the formal and legal framework of the organization in such a case remains only an official record, and its actual functioning and success depends on trends, developments in technology and sometimes just the mood of the stakeholders. The main purpose of this article is to examine the current state of the relevant publications, and identify the key megatrends that most determine the evolution of the view of modern organizations.
Keywords: Megatrends; organisation; globalization; outsourcing; coinnovation; coopetition; crowdsourcing; crowdfunding